Assessing the distribution of total Fe, Cu, and Zn in tropical peat at an oil palm plantation and their relationship with several environmental factors - Heru Bagus Pulunggono; Lina Lathifah Nurazizah; Moh Zulfajrin; Syaiful Anwar; Supiandi Sabiham (Journal of Degraded and Mining Lands Management, 2022)
Extensive utilization of fragile tropical peatlands ecosystem encourages a better understanding of spatiotemporal micronutrients distribution. The distribution of total Fe, Cu, and Zn in peat and their relationship with environmental factors were studied under oil palm plantation, Pangkalan Pisang, Koto Gasib, Riau, Indonesia. Peat samples were taken compositely inside the block using a combination of six factors, including a) the oil palm age (<6, 6-15, >15 years old), b) the peat thickness (< 3 and >3 m), c) season (rainy and dry), d) the distances from the secondary canal (10, 25, 50, 75, 100, and 150 m), e) the distances from an oil palm tree (1, 2, 3, and 4 m), and f) the depth of sample collection (0-20, 20-40, and 40-70 cm from the peat surface). Total Fe, Cu, and Zn were determined by the wet digestion method. These micronutrients observed in this study possessed high variability; however, they were within the expected range in tropical peatland. The entire micronutrients were statistically different by oil palm age, peat thickness, and distance from canal. Meanwhile, total Cu and Zn were also significantly different at each season. The oil palm age, peat thickness, and distance from the canal were the common factors controlling total Fe, Cu, and Zn in peat significantly. Moreover, total Cu and Zn were also dictated by season, distance from the oil palm tree, and depth of sample collection. Based on visual interpretation in PCA (principal component analysis), all micronutrients were categorized into two groups, separated by 2 m distance from the oil palm tree and 20 cm depth from the soil surface. Our study also highlights the dominance of the dilution over the enrichment process in peat, which requires further research to formulate micronutrients fertilization, especially for an extended cultivation time.